The Effects Of Vocabulary Mastery and Logical Thinking towards Student’s Listening Skill at Private Vocational High Schools in East Jakarta. - Wita Wulandari (Scope : Journal of English Language Teaching, 2018)
The aim of this research is to find out the effect of vocabulary mastery and logical thinking towards the students’ listening skill. The research was conducted at SMK. The population in this research is 450 students of Grade XI, with 90 sample students. The method used in this research is a survey method. The data are obtained from the vocabulary test, logical thinking test and listening test. The hypothesis test are showed : 1.) There are any significant effects vocabulary mastery and logical thinking towards listening skill. That is proved by Sig. 0,000 < 0,05 and Fo = 19,049. Based on the result of the research, it proves that students’ vocabulary and logical thinking mastery give positive contribution towards the students’ listening skill.Keywords : Vocabulary Mastery, Logical Thinking, Listening Skill,